PERAN PESANTREN DALAM MODERASI BERAGAMA DI ASRAMA PELAJAR ISLAM TEALREJO MAGELANG JAWA TENGAH INDONESIA - Suprapto Suprapto; Eny Rahmawati; Bambang Sumardjoko; Waston Waston (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2022)
The Tegalrejo Islamic Student Dormitory Boarding School, Magelang, Central Java, is an Islamic educational institution with an integrated implementation of religious education with the studies of the yellow book (turath) which synergizes with public school education, using curriculum 13. Apart from being Salafi, The API Islamic Boarding School understands that Ahlussunnah Wal Jamaah (Aswaja) strongly emphasizes the attitude of religious moderation. Education as a fundamental aspect includes Islamic boarding schools as a forum to galvanize the younger generation of Islam who are ready to accept the relay of struggle from previous leaders and scholars. Pesantren is a fortress to prevent the degradation of the nation's moral values. The purpose of this study is to find out the role of ustadz/ustadzah in giving their teachings to students in terms of moderation and eliminating intolerant behavior. The method used is qualitative by conducting observations, interviews, and collecting documentation, as well as distributing questionnaires as supporting data. The results of this study describe the application of the school curriculum at the APi Tegalrejo Islamic boarding school Magelang combined with the study of the yellow book (classic) as a reference in terms of religious knowledge. Thus giving birth to an attitude of religious moderation among students under the auspices of the pesantren. In this study, it was found as a form of contribution that the use of educational curriculum 13 which was integrated with the study of classical book studies, based on Salafi and Aswaja-oriented, was able to provide insight to santri students at the API Boarding School to become moderate students, this was shown by the students being able to follow the dynamics developmental life in society which involves issues of religion, social, culture, science, business skills and technology today.